Application of the Hanifida Method in Improving Memorization of Short Surahs in Students of SD Negeri 145 OKU - Yusmarita, Yusmarita (Indonesian Journal of Research in Islamic Studies, 2024)
At the elementary school level, memorizing short chapters of the Qur'an is one of the challenging materials to learn, especially for students. In students, the delivery of short surah Al_Qur'an material that has been done by teachers at school with the lecture method makes this material difficult for students to understand and remember. This study aims to determine the application of the hanifida method in improving the memorization of short surahs in SD Negeri 145 OKU students. This research is a Classroom Action Research (PTK). The subjects in this study were third grade students, totaling 20 children at SD Negeri 145 OKU. Data collection techniques used in this study were using test and non-test techniques. Data analysis includes observation sheets for learner and teacher activities, as well as written test results. The results showed that the application of the Hanifida method in memorizing short sentences can optimize memorization results. This is indicated by significant changes in students' enthusiasm in following the learning material and the percentage of memorization results. The implementation of the study of the application of the Hanifida method to increase memorization speed took place as planned.